O wybranych funkcjach trybu rozkazującego zwrotów frazeologicznych - Witkowska, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The aim of this paper is to discuss several secondary problems related to the description of paradigms of Polish phraseological units with a verbal component, i.e. indication of the selected function of their imperative forms. The considerations focus on two general issues. Firstly, they present the possible contexts of using said phrases and, secondly, they verify the hypothesis that verbal phraseological units inherit the properties of verbs with regard to the possibility of occurrence in certain imperative form functions.